H02 Low levels of transforming growth factor β1 in Huntington's disease peripheral macrophages and brain glial cells. (16th November 2010) - Silvia, A; Orobello, S; Martino, T; Griguoli, A M; Amico, E; Squitieri, F
Abstract : Background: Huntington's disease (HD) is a neurodegenerative disorder caused by a CAG expansion mutation in huntingtin (HTT). Mutant HTT induces cell death modulating several molecular pathways, including cell signalling, transcriptional machineries, and neurotrophins production and release. Recently, we have reported an early defect in transforming growth factor (TGF)β1 production in HD subjects and in two HD mouse models (R6/2 and YAC128). TGFβ1 is a pleiotropic cytokine with an established neuroprotective function as well as a powerful anti-inflammatory role. Aim: Since TGFβ1 is predominantly expressed in the immune system and since myeloid derived immune cells (ie, glial cells) are implicated in neurodegeneration, we investigated the levels of this cytokine in immortalised human astroglial cell lines expressing wild-type (SVGp12-25Q) and mutant (SVGp12-72Q) HTT-exon1, and in macrophages from HD subjects and R6/2 mice. Methods: We analysed the levels of TGFβ1 within cell lines by flow cytometry and by quantitative real time PCR. All HD subjects (n=28) were clinically and genetically evaluated and age matched with health controls (n=14). Results: Our analysis showed significant reduced levels of TGFβ1 in human and mouse HD macrophages, and in human immortalised HD glial, compared with wild-type cells. Interestingly, TGFβ1 levels in human macrophages depended on the disease stage. Such scenario was confirmed by experiments in HD mice who showed significant low levels of the cytokine at the presymptomatic stage. Conclusion: While confirming a TGFβ1 related dysfunction in peripheral and brain tissues in HD, we remark the potentiality for searching novel possible progression related markers in HD.